INSTITUTIONAL STRENGTHENING AND MANAGEMENT OF VILLAGE-OWNED ENTERPRISES TO IMPROVE THE WELFARE OF VILLAGE COMMUNITIES - M. Zulfan Hakim; Muhammad Ilham Arisaputra; Andi Tenri Famauri; Ariani Arifin (UNTAG Law Review, 2020)
Village-Owned Enterprises exists as a populist economic institution that is expected to be able to be a means to improve the welfare of rural communities. The success of Village-Owned Enterprises management is expected to help create jobs, provide prosperity and prevent urbanization because the existence of Village-Owned Enterprises is sufficient to be a source of livelihood for the young generation of villages. Although in its implementation many obstacles were encountered by the Village-Owned Enterprises manager, but it did not reduce the enthusiasm and intention to achieve the goals that had been aspired to for the improvement of the welfare of the village community.